ДОСЛІДЖЕННЯ ЕНЕРГОЕФЕКТИВНОСТІ ОБРОБКИ ІМПУЛЬСНИМ БАР’ЄРНИМ РОЗРЯДОМ ВОДИ В КРАПЕЛЬНО-ПЛІВКОВОМУ СТАНІ - Берека, В.О.; Божко, І.В.; Кондратенко, І.П. (Інститут електродинаміки НАН України, Київ, 2021)
The energy efficiency of a pulsed barrier discharge in air was investigated when it treated a model water sample in a drop-film state containing an organic dye (methylene blue) with an initial concentration of 50 mg/l. The water consumption was 4 l/min, the characteristic droplet diameter was ~1 mm. Water treatment was carried out in a coaxial discharge chamber with a gas gap of 3.2 mm and additionally in an ozonation chamber. The discharge was generated by short ~ 100 ns voltage pulses of ≈26 kV, which provided a current density with an amplitude of ≈ 1.3 A/cm2 and a pulse energy of ≈ 140 mJ. The time of decomposition of the impurity and the energy efficiency of the discharge were investigated as a function of the pulse repetition rate of 25−300 Hz. The discharge had the highest energy efficiency at frequencies of 25-50 Hz, at which the energy yield corresponding to 50% decomposition of the impurity is about 100 g/kW h. It is shown that most of ozone, one of the main oxidants generated by the discharge, dissolves in water in the discharge chamber. The concentration of ozone at the outlet from the discharge chamber can reach 2.2 mg/l. The remaining ozone is absorbed by the model solution (about 60%) in the ozonization chamber. References 16, figures 7.